(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
Leptospirosis remains as a major public health problem nowadays, mainly affecting vulnerable communities with low socioeconomic resources. In this study, the molecular detection of pathogenic leptospires from environmental samples (water and mud) from northern Argentina (Formosa, Salta, Santiago del Estero, Misiones and Chaco provinces) is described. Samples were obtained from regions with varied climatological features, all inhabited by vulnerable communities. From the 89 samples that were analyzed, 24.7% showed molecular evidence of the presence of pathogenic leptospires. Prevalence by sample type was: 27.8% in water samples and 11.8% in mud samples. All the sampled regions showed at least one positive sample. This result highlights the need of further research regarding leptospirosis in different regions of Argentina.